Upaya Peningkatan Ketahanan Pangan Dengan Menggunakan Pupuk Organik Cair Di Desa Astanalanggar Kabupaten Cirebon - Farhan, Herry; Pribadi, Riky; Dewi, Rani; Nuraeani, Yeni (Universitas Majalengka, 2024)
educational facilities in rural areas. The goal of the Community Service Program (KKN-T) in Sadapaingan Village is to improve community literacy. The program aims to encourage the growth of a culture of literacy in Sadapaingan Village by providing engaging reading facilities and activities for children and adolescents. The program also develops village reading corners as centers for literacy activities accessible to the community. Overall, the KKN-T program has made a positive contribution to the Sadapaingan Village community. The literacy program fostered children's interest in reading, nutrition education raised public awareness of stunting prevention, and strengthened social ties and fostered a sense of community togetherness. Active community participation and support from village officials, relevant agencies, and KKN-T students are key factors in the success of this program. The implementation of the program's results is expected to continue to provide benefits and improve the community's quality of life in a sustainable manner.